The Protective Effect of Sulforaphane on Dextran Sulfate Sodium-Induced Colitis Depends on Gut Microbial and Nrf2-Related Mechanism - He, Canxia; Gao, Mingfei; Zhang, Xiaohong; Lei, Peng; Yang, Haitao; Qing, Yanping; Zhang, Lina (Frontiers in Nutrition, 2022)
Sulforaphane (SFN), an isothiocyanate existing in cruciferous vegetables such as broccoli and Brussels sprouts, has a variety of biological functions. This study was undertaken to assess the potential efficacy of SFN in improving dextran sulfate sodium (DSS)-induced ulcerative colitis (UC) in mice, and to elucidate the underlying mechanisms. UC was induced by administrating 2% DSS in drinking water for 7 days. Male C57BL/6 mice were treated with mesalazine (50 and 100 mg/kg body weight) and various doses of SFN (2.5, 5, 10 and 20 mg/kg body weight). In the DSS-induced mice, shortened colon length, increased disease activity index (DAI) scores, pathological damage, increased proinflammatory cytokines and decreased expression levels of tight junction proteins were observed, most of which were alleviated by SFN treatment. SFN also partly restored the perturbed gut microbiota composition and increased the production of volatile fatty acids (especially caproic acid) induced by DSS. The heatmap correlation analysis indicated that Lactobacillus johnsonii, Bacteroides acidifaciens, unclassified Rikenellaceae RC9 and unclassified Bacteroides were significantly correlated with disease severity. Nuclear factor (erythroid- derived 2)- like 2 (Nrf2), Signal Transducers and Activator of Transcription 3 (STAT3) and Phase II enzyme UDP-glucuronosyltransferase (UGT) were involved in the protective effect of SFN against DSS-induced colitis. All these results showed that SFN might serve as a nutritional agent for protecting against the damages in ulcerative colitis.